FILSAFAT PENDIDIKAN ISLAM PERSPEKTIF FILOSOFIS, TUJUAN DAN METODE PENDIDIKAN ISLAM - Su'eb (Jurnal Subulana, 2022)
The Islamic view of humans and life is formed on the principle of harmony and a combination of the senses, mind and heart of a believer. The harmony of the three is the most fundamental epistemological base in Islamic philosophy. Thoughts with appreciation are used as instruments or tools in conducting research based on this epistemological framework. The activity of thinking is considered a sacred duty in Islam, and thinking is a tool for giving birth to a progressive life, which is formed by absorbing values ??from reality. Islamic education must be a process of producing “good human beings” who are able to maximize their full potential. Usually educational methods must reflect integrative-interconnective nuances that are able to stimulate the development of potential to the fullest.